Giving well the ethics of philanthropy - Illingworth, Patricia M. L., 1954-; Pogge, Thomas, 1953-; Wenar, Leif. (New York ; Oxford : Oxford University Press, 2011)
Here, a trio of editors bring together an international group of philosophers, social scientists, lawyers and practitioners to identify and address the moral questions arising today in the practice of philanthropy. The topics discussed include the psychology of giving, the reasons for and against a duty to give, and much more.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Dec. 17, 2010).
Keywords: Charities -- Moral and ethical aspects